2013
DOI: 10.3892/mco.2013.138
|View full text |Cite
|
Sign up to set email alerts
|

Survivin, Ki-67 and tumor grade as predictors of response to docetaxel-based neoadjuvant chemotherapy in locally advanced breast cancer

Abstract: The response rates to neoadjuvant chemotherapy (NAC) in patients with locally advanced breast cancer (LABC) may vary and the risks may outweigh the benefits in poorly selected patients. This study investigated whether survivin expression, high-level Ki-67 expression, estrogen-receptor (ER) tumor status and high tumor grade are able to predict response to docetaxel-based NAC in LABC patients, in order to perform breast-conserving surgery. In this study, 68 patients (IIb-IIIb) completed 4–6 cycles of TAC (75 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The similar situation is with the association between high survivin expression and Ki67 expression. While some studies [38] showed the same results as here, others showed there was no significant association between survivin and Ki67 [31, 39].…”
Section: Resultssupporting
confidence: 81%
“…The similar situation is with the association between high survivin expression and Ki67 expression. While some studies [38] showed the same results as here, others showed there was no significant association between survivin and Ki67 [31, 39].…”
Section: Resultssupporting
confidence: 81%
“…Supporting this hypothesis, findings have suggested that tumors with high histologic grade may predict the pCR in anthracyclinecontaining neoadjuvant therapy. [10][11][12] In the current study, hormone receptor negativity, HER-2neu positivity, and higher grade scores are statistically significant factors that affect pathological complete response development, corroborating previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, several studies could not detect any association between negative ER expression and anthracycline-based chemotherapy response. 11,12 The HER2-neu gene expression was reported to be positive in approximately 30% of breast cancers. 9 Increased expression of HER-2neu is associated with resistance to docetaxel treatment in vitro, also trastuzumab treatment is thought to sensitize breast cancer cells to docetaxel.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have established molecular markers, which are associated with distinct histopathological features, the response to adjuvant therapy and/or the clinical outcome of breast cancer (2)(3)(4)(5)(6)(7). Furthermore, the following clinicopathological factors are considered to be useful markers for predicting prognosis and identifying therapeutic targets in patients with advanced breast cancer: American Joint Committee on Cancer (AJCC) stage, histological grade, oestrogen receptor (ER) and progesterone receptor (PR) expression, human epithelial growth factor receptor 2 (HER2) amplification, p53 expression and Ki-67 labelling index (2)(3)(4)(5)(6). Based on data obtained from molecular or immunohistochemical (IHC) analyses, breast cancer is classified into four major subtypes: Luminal A, luminal B, basal-like and HER2-positive (7).…”
Section: Introductionmentioning
confidence: 99%